Influencing Factors Associated With Mental Health Outcomes Among Dental Medical Staff in Emergency Exposed to Coronavirus Disease 2019: A Multicenter Cross-Sectional Study in China - Chen, Yaopian; Li, Wei (Frontiers in Psychiatry, 2021)
Background: The epidemic infection of coronavirus disease 2019 (COVID-19) may have a profound impact on dentistry, mainly due to the mode of transmission of the pathogen, which poses a risk to almost all dental operations. Therefore, this study aimed to investigate the prevalence and influencing factors of anxiety, depression, perceived stress, and acute stress disorder among dental medical staff in emergency situations during the COVID-19 epidemic. Methods: From April 3, 2020, to April 10, 20204, a multicenter cross-sectional study was conducted among 808 first-line dental professionals at an emergency department in mainland China. A self-designed questionnaire was used to collect general demographic information. The 7-item Generalized Anxiety Disorder Scale (GAD-7), 9-item Patient Health Questionnaire (PHQ-9), 10-item Perceived Stress Scale (PSS-10), and Acute Stress Disorder Scale (ASDS) were used to assess the severity of symptoms of anxiety, depression, perceived stress, and acute stress disorder (ASD), respectively. Results: The prevalence rates of depression, anxiety, perceived pressure, and ASD among the frontline dental medical staff were 46.4, 36.3, 65.2, and 1.1%, respectively. The frontline dental medical staff who were working in the Wuhan area reported experiencing more anxiety (p = 0.038) and perceived stress (p < 0.001) compared with those who were not working in the Wuhan area. The frontline dental medical staff who were working in a general hospital reported experiencing more dissociation symptoms (p = 0.001) compared with those working in a specialized or private hospital. Individuals with a past medical history reported experiencing more anxiety (p = 0.009), depression (p < 0.001), and perceived stress (p = 0.003) than those without, and individuals with lower levels of education showed higher levels of anxiety (p = 0.038). Binary logistic regression analysis results (after controlling for other confounders) suggested that having a past medical history was a risk factor for both anxiety (p = 0.002; OR = 2.441; 95% CI, 1.384–4.306) and perceived stress (p = 0.001; OR = 1.417; 95% CI, 1.145–1.754). Conclusions: The prevalence of mental symptoms was high among the first-line emergency dental staff. Male sex, working in the Wuhan area, working in a general hospital, a past medical history, and lower levels of education were risk factors. Therefore, we need to pay close attention to the mental health problems of frontline dentists during the COVID-19 outbreak and adopt active preventive strategies to maintain their physical and mental health.